(untitled) (Journal of Atomic and Molecular Sciences, 2014)
By using two model potentials chosen, the second outermost back rescattered ridges (BRR) of the two-dimensional (2D) momentum spectra of H^- ion in the linear polarization laser fields are studied under the strong-field approximation (SFA). The results show that the polarization potentials in the two model potentials have little effect on the 2D momentum spectra, the number of BRR increases and the fluctuation of angular distributions along the second BRR decreases with the increase of the laser intensity, but the accurate electron-atom elastic scattering cross sections can be retrieved directly along the second outermost BRR by the polynomial fitting method.